2001
DOI: 10.1111/j.1572-0241.2001.03884.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, biliary lipids, and gallstones in obese subjects

Abstract: Our findings demonstrate that low levels of physical activity are associated with gallstone formation. Our study also suggests that a possible mechanism for the protective effect of physical activity on gallstone formation is the lowering of biliary cholesterol levels, thus preventing cholesterol from precipitating in the bile. In addition, our data suggest that sport activity is a more effective form of physical activity than working and leisure activities in the prevention of gallstone disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 30 publications
4
21
0
Order By: Relevance
“…Chuang et al [59] studied a small sample of 53 obese women who were undergoing gastric bypass surgery. After allowing for BMI and high-density lipoprotein (HDL) cholesterol levels, sport participation, but not occupational or leisure activity, reduced the odds of discovering gallstones during surgery.…”
Section: Cross-sectional Analyses Of Habitual Physical Activity and Gmentioning
confidence: 99%
“…Chuang et al [59] studied a small sample of 53 obese women who were undergoing gastric bypass surgery. After allowing for BMI and high-density lipoprotein (HDL) cholesterol levels, sport participation, but not occupational or leisure activity, reduced the odds of discovering gallstones during surgery.…”
Section: Cross-sectional Analyses Of Habitual Physical Activity and Gmentioning
confidence: 99%
“…Carrasco [27] examined predictors of weight loss success in 31 RYGB patients, 6 months after surgery. In a similar study of 199 LAGB patients, Larsen et al [31] found exercise was related to mental health but not to BMI reduction or physical health.…”
Section: Included Studiesmentioning
confidence: 99%
“…Data were pooled for weight loss from four studies [23,24,27,29]. To allow for comparisons across these studies, participants Fig.…”
Section: Meta-analysismentioning
confidence: 99%
“…Case-control study (2)(3)(4)(5) Cross-sectional study (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Gallstones in pregnancy (21)(22)(23) Letter/editorial/news/note/comment (24)(25)(26)(27)(28)(29)(30) Meta-analysis No protocol Eligibility criteria 6 Specify study characteristics (e.g., PICOS, length of follow-up) and report characteristics (e.g., years considered, language, publication status) used as criteria for eligibility, giving rationale.…”
mentioning
confidence: 99%